2018
DOI: 10.1108/jedt-08-2017-0081
|View full text |Cite
|
Sign up to set email alerts
|

Towards reliable prediction of academic performance of architecture students using data mining techniques

Abstract: PurposeIn recent years, there has been a tremendous increase in the number of applicants seeking placement in the undergraduate architecture programme. It is important to identify new intakes who possess the capability to succeed during the selection phase of admission at universities.Admission variable (i.e. prior academic achievement) is one of the most important criteria considered during selection process. The present study investigates the efficacy of using data mining techniques to predict academic perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 54 publications
0
20
0
1
Order By: Relevance
“…Though, this finding seems not contradictory to the earlier reported ones as both high school grades and the ongoing semester course grades still refer to prior academic achievement of the students in some sense. The findings reported by Aluko, Daniel, Oshodi, Aigbavboa and Abisuga (2018); Opstad, Bonesrønning and Fallan (2017) corroborate this point. Aluko et al (2018) utilised more sophisticated statistical tools such as logistic regression and support vector machine learning to establish high correction between prior academic achievement and performance.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Though, this finding seems not contradictory to the earlier reported ones as both high school grades and the ongoing semester course grades still refer to prior academic achievement of the students in some sense. The findings reported by Aluko, Daniel, Oshodi, Aigbavboa and Abisuga (2018); Opstad, Bonesrønning and Fallan (2017) corroborate this point. Aluko et al (2018) utilised more sophisticated statistical tools such as logistic regression and support vector machine learning to establish high correction between prior academic achievement and performance.…”
Section: Introductionmentioning
confidence: 60%
“…university (Ayán & García, 2008), high school students (Casillas et al, 2012); the field of study, e.g. accounting (Duff 2004), mathematics (Hailikari et al, 2008), economics (Opstad et al, 2017), and architecture (Aluko et al, 2018). In several of these studies, researchers have used students' test scores on standardised tests, high school grades and entrance exams (Aluko et al, 2018;Casillas et al, 2012;Duff 2004;Newman Ford et al, 2009) while others have used students previous semester/year grades (Ayán & García, 2008;Engerman & Bailey, 2006;Martin et al, 2016;Zakariya, 2016) or a special exam on problem-solving (Hailikari et al, 2008) to assess prior knowledge.…”
Section: The Conceptualisation Of Prior Knowledgementioning
confidence: 99%
“…Using pre-enrollment features to predict students' academic achievement is significant, especially if the prediction is to be performed at an early stage (Alturki et al, 2020). Previous GPA is one of the most popular used features for predicting academic success (Abu Saa, 2016;Aluko et al, 2018;Garg, 2018;Huang & Fang, 2013;Kabakchieva, 2013;Kovačić, 2010;Osmanbegović & Suljic, 2012;Pal & Pal, 2013;Thai-Nghe et al, 2007). Academic language skills have also been widely used for predicting academic success (Abu Saa, 2016;Asif et al, 2017;Badr et al, 2016;Bani-Salameh, 2018;Thai-Nghe et al, 2007).…”
Section: Related Work On Predictions In Higher Educationmentioning
confidence: 99%
“…Aluko, Daniel, Shamsideen Oshodi, Aigbavboa, & Abisuga, [3] compared the prediction accuracy of Support vector machine and logistic regression using a sample size of 102 architecture students for predicting the performance of students in academics and found that Support vector machine classifier is better than logistic regression in predicting students' academic performance. Umer, Susnjak, Mathrani, & Suriadi, [14] have used three Machine learning classification algorithms to predict the performance of students by recording their weekly performance in MOOCS environment.…”
Section: Review Of Literaturementioning
confidence: 99%